Pemilu Berintegritas Menuju Demokrasi Yang Sehat - Firman Amir (Peneliti.net, 2023)
Democracy wants the ruling government to be actually elected by the people, so that this power is actually a service to carry out the people's mandate, to then carry out the aspirations and prosper the people.